Usefulness of Micro Enterprise Development (MED) Model - Neupane, Rabindra K.; Luitel, Madan Kumar (DEPAN, 2023)
This article evaluates the usefulness of micro-enterprise development (MED) model to its primary beneficiaries i.e. micro-entrepreneurs for their enterprise’s performance growth. It is a tool for enterprise creation and development implemented through a program named MEDEP by Ministry of Industry. Field survey of micro-entrepreneurs of Banepa and Chaurideurali has been conducted to collect their opinion on the benefits realized through MED model for their enterprise performance growth. Descriptive research design is used to describe the benefits entrepreneurs have realized from the model. Both the results from descriptive and inferential data analysis have proved the positive utility of MED model for enterprise performance growth, although the relationship between MED model and Enterprise performance growth is significantly moderated by industry types. Conclusively, the model is beneficial to start-up enterprises for growth and sustainability. Therefore, the model is useful to be replicated by other standalone skill and enterprise training providers in Nepal